Penerapan Holt-Winters untuk Prediksi Harga Beras di Sumatera Utara - Daniel Bakkara; Imelda Sri Dumayanti; Edward Rajagukguk (Universitas Methodist Indonesia, 2024)
In the base price of rice and world rice prices, crop failures that reduce rice stocks, and dependence on rice imports which are potential causes of rising rice prices. The use of the Holt-Winters method in predicting rice prices in North Sumatra has the potential to make a positive contribution to increasing economic stability and the welfare of farmers and rice consumers in the region. The results of applying the Holt-Winters method to predict rice prices in North Sumatra for 2023 show an upward trend in prices for both premium and medium rice. In this study, the parameter values are α = 0.8, β = 0.7, and γ = 0.3. The prediction of premium rice prices starts at Rp 13,783.995 in January and consistently increases to Rp 17,234.625 in December. The price of medium rice is also projected to increase, starting from Rp 12,463.088 in January and rising to Rp 15,094.911 in December. The multiplicative Holt-Winters method can predict rice prices in North Sumatra well, with forecasting accuracy values using the MAPE method of 9.17% for premium rice and 5.86% for medium rice. The significance level of the forecasting results conducted in this study falls into the Excellent category.